Automatic Roadway Backfilling of Caving Gangue for Cutting Roofs by Combined Support on Gob-Side Entry Retaining with No-Pillars: A Case Study - Shengrong Xie; Xiaoyu Wu; Dongdong Chen; Yaohui Sun; Junchao Zeng; Qing Zhang; Chunwei Ji; Qiong Cheng; En Wang; Yuxin Ren (Advances in Materials Science and Engineering)
Automatic roadways on gob-side entry retaining with no-pillars are used for longwall mining technology. The mining technology with no-pillars can recover coal pillar resources and reduce the amount and cost of roadway excavations. Automatic roadway technology for cutting roofs by combined support on gob-side entry retaining with no-pillars is adopted for the condition of thick immediate roof and medium-thick coal seam mining, cutting off the immediate roof and the main roof on the gob by combined support. The fractured roof forms gangue blocks to fill the gob and loads the overlying strata. The gangue control system is placed on the roadside, which controls the caving gangue to form a gangue rib. In this paper, the viewpoints and key technologies (the roof-cutting technology, the reinforcement and support technology, the gangue rib control technology, and the auxiliary support technology) of automatic roadway technology for cutting roofs by combined support on the gob-side entry retaining with no-pillars are introduced. Furthermore, the formation and control process are explained. The numerical simulation is used to simulate and analyze the roof hanging and the roof cutting structures. In addition, a field engineering test is performed. The field test shows that automatic roadway technology for cutting roofs by combined support on gob-side entry retaining with no-pillars is feasible. This process uses construction techniques and technologies to meet on-site production needs. The combined support has high resistance strength and is shrinkable. In engineering applications, the combined support has a low damage rate. The deformation of the automatic roadway with gob-side entry retaining is small, and the control effect is significant.